PENGARUH HARGA DAN PROMOSI TERHADAP BRAND AWARENESS PADA MALL UKM KOTA CIREBON - Fariza, Muthia; Nurhajijah, Sitta; Puspita, Adelia; Nurbaeti, Allifah (CV. Kalimasada Group, 2023)
This study aims to analyze the efforts of the Cirebon City UKM Mall in knowing the effect of price and promotion on brand awareness. In this study the research method used is quantitative data. The population in this study was five hundred and six recovered five (565) and the sample of this study were customers who had purchased products provided by the Cirebon City UKM Mall. The method used in this study is the validity test, reliability test, multiple linear regression analysis technique, F test, T test, and analysis of the coefficient of determination. The research data was processed using SPSS 26 software. The independent variables in this study were price (X1) and promotion (X2). The variable associated with this study is Brand Awareness (Y). The results of this study indicate that the price and promotion variables simultaneously have a significant effect on brand awareness. Price and promotion variables also have a significant influence on brand awareness.